"QUILCA" AND "ROCK ART", DISQUISITIONS ABOUT CONTEXT OF THE ART, ARCHEOLOGY AND PERUVIAN SCIENCE - Echevarría López, Gori Tumi (2017)
Based on a historical review of the terminology that describes the so-called “rock art”, this essay examines and questions the usefulness of this term against the indigenous category of “quilca”, whose epistemological validity is weighted for the description and study of The graphic manifestations in rock or earth, such as pictograms, petroglyphs, geoglyphs, or furniture art with rock tradition. It is concluded that the category composed of “rock art” constitutes an ontological limitation for the compression of the graphic phenomenon associated with rock in the Andes.